Microfluidic temperature gradient focusing by electrokinetically induced joule heating - Ge, Zhengwei. (2013)
Microfluidics has been developed over the past decade due to its promising applications in biotechnology, medicine, and chemistry. Towards these applications, enhancing concentration sensitivity and detection resolution are needed to meet the detection limits because of the very dilute solution, ultra-small volumes and short detection length in micro-devices. A variety of microfluidic concentration techniques of analytes has been developed. Among them, temperature gradient focusing (TGF) is a recently developed field gradient focusing technique. It concentrates and separates the sample analytes at their stagnant points, where the analyte’ electrophoretic motion is balanced against the bulk flow of buffer solution. The simple structure and the high concentration in a relatively short channel make TGF well suitable for integrated microfluidic systems. Furthermore, using Joule heating for generating temperature gradient shows more advantages than using external heating. The former consumes less power, simplifies the device construction and operation, and makes the whole device more portable without need of bulky external heating unit. This dissertation presents a fundamental, systematic and in-depth investigation on Joule heating induced TGF to provide better understanding of the physical processes associated with TGF and to improve the concentration enhancement.